2012
DOI: 10.1038/nn.3289
|View full text |Cite
|
Sign up to set email alerts
|

A subpopulation of nociceptors specifically linked to itch

Abstract: Itch-specific neurons have been sought for decades. The existence of such neurons is in doubt recently due to the observation that itch-mediating neurons also respond to painful stimuli. Here, we genetically labeled and manipulated MrgprA3+ neurons in dorsal root ganglion (DRG) and found that they exclusively innervate the epidermis of the skin and respond to multiple pruritogens. Ablation of MrgprA3+ neurons led to significant reductions in scratching evoked by multiple pruritogens and occurring spontaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
659
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 511 publications
(696 citation statements)
references
References 50 publications
32
659
2
3
Order By: Relevance
“…49,50) A more recent study using conditional transgenic mice revealed that ablation of MrgprA3 + drG neurons led to substantial reductions in scratching evoked by multiple pruritogens and occurring spontaneously under chronic itch conditions. 51) However, pain sensitivity remained intact in these mice. Moreover, mice in which transient receptor potential vanilloid 1 (trPV1) was exclusively expressed in MrgprA3 + DRG neurons exhibited itch, but not pain, behavior in response to capsaicin.…”
Section: Mas-related G-protein Coupled Receptors (Mrgprs)mentioning
confidence: 89%
“…49,50) A more recent study using conditional transgenic mice revealed that ablation of MrgprA3 + drG neurons led to substantial reductions in scratching evoked by multiple pruritogens and occurring spontaneously under chronic itch conditions. 51) However, pain sensitivity remained intact in these mice. Moreover, mice in which transient receptor potential vanilloid 1 (trPV1) was exclusively expressed in MrgprA3 + DRG neurons exhibited itch, but not pain, behavior in response to capsaicin.…”
Section: Mas-related G-protein Coupled Receptors (Mrgprs)mentioning
confidence: 89%
“…However, overall TRPV1 expression in the central nervous system (CNS) is considerably lower than in the DRG (Cavanaugh et al, 2011;Han et al, 2012;Sanchez et al, 2001;Szabo et al, 2002). Indeed, some studies have failed to detect the presence of TRPV1 in the CNS (Benninger et al, 2008;Caterina et al, 2000;Szallasi, 1995;Tominaga et al, 1998) possibly due to complexity in genes and strain-related variations (Sanchez et al, 2001;Sudbury et al, 2010).…”
Section: Localisationmentioning
confidence: 99%
“…One gene is expressed in a genetically defined set of neurons. Another gene codes for the neurotoxin that kills the cells with a known genetic identity [166][167][168]. Saporin, a toxin protein from a plant Saponara officinalis, can also be used for cell type or circuit-specific ablation.…”
Section: Cell-specific Neurotoxinsmentioning
confidence: 99%